Momentary severity of psychotic symptoms predicts overestimation of competence in domains of everyday activities and work in schizophrenia: An ecological momentary assessment study. (April 2022) - Gohari, Ellaheh; Moore, Raeanne C.; Depp, Colin A.; Ackerman, Robert A.; Pinkham, Amy E.; Harvey, Philip D.
Highlights: People with schizophrenia who were more commonly home and alone overestimated their competence in domains of everyday activities and work skills. Momentary experiences of psychotic symptoms was also correlated with overestimation. These data suggest that people with schizophrenia may rely on their self generated ideas to a greater extent than on objectively verifiable information. Abstract: Objectives: Schizophrenia participants generate self-reports of their competencies that differ from objective information. They may base their reports on momentary moods or experiences rather than objective data. Theories of delusion formation implicate overconfidence during self-assessment as a cause. Methods: Ecological momentary assessment (EMA) was used to sample activities and experiences in 101 participants with schizophrenia up to 3 times a day for 30 days. Each survey asked where and with whom they were, what they were doing, and moods and psychotic symptoms they were experiencing. Self-reports and observer ratings of competence in work and everyday activities were collected. Results: Being home was associated with self-reports of better functioning in activities and work skills ( p <.001) and being alone correlated with better self-reported functioning in activities ( p <.001). Participants who reported more occurrences of hearing voices,  paranoid ideation, and other psychotic symptoms reported their functioning as better ( p <.001). Implications: Schizophrenia was marked by a disconnect between momentary activities and self-assessments. Being home more was associated with better self-reported functioning on tasks that are only performed away from home. Psychotic  symptoms were associated with overestimation, consistent with previous theories positing that overconfidence and suspension of plausibility assessment may be associated with psychotic experiences.